Liquid crystal polymer material as well as preparation method and application thereof

By adding titanium dioxide and PCT resin to the liquid crystal polymer resin and controlling its mass ratio, the problems of low whiteness and high-temperature yellowing of the thermogenic liquid crystal polymer substrate are solved, and liquid crystal polymer materials with high whiteness and excellent high-temperature yellowing resistance are achieved, which are suitable for LED components and other products.

CN119875389APending Publication Date: 2025-04-25ZHUHAI WANTONG SPECIAL ENG PLASTICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311375477.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing thermal liquid crystal polymer substrate has a dark base color, which makes it low whiteness, making it difficult to use as an LED component material with high whiteness requirements, and is prone to yellowing in high temperature environments.

Method used

By adding titanium dioxide and PCT resin to the liquid crystal polymer resin and adjusting the mass ratio of titanium dioxide to the PCT resin, a high-white liquid crystal polymer material is obtained, and its high-temperature yellowing performance is excellent.

Benefits of technology

The high whiteness and excellent high temperature yellowing resistance of liquid crystal polymer materials are achieved, making them suitable for the production of LED components and other parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004507842820000051
    Figure BDA0004507842820000051
  • Figure BDA0004507842820000061
    Figure BDA0004507842820000061
  • Figure BDA0004507842820000062
    Figure BDA0004507842820000062
Patent Text Reader

Abstract

The invention relates to a liquid crystal polymer material as well as a preparation method and application thereof. The liquid crystal polymer material comprises the following components: liquid crystal polymer resin, titanium dioxide and PCT resin. According to the invention, the liquid crystal polymer resin is used as matrix resin, a certain amount of titanium dioxide is added, a certain amount of PCT resin is added, and the mass ratio of titanium dioxide to PCT resin is regulated to be within a specific range, so that the high-whiteness liquid crystal polymer material can be obtained, and the high-temperature yellowing resistance of the liquid crystal polymer material is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of engineering plastics, and more specifically, to a liquid crystal polymer material and a preparation method and application thereof. Background Art

[0002] Compared with incandescent light sources, LED lights have many advantages such as lower voltage, lower energy consumption, smaller size, longer service life, higher brightness, and shorter response time. In recent years, LED lights have been popularized in all aspects of life, such as traffic signals, interior and exterior lighting, mobile phone displays, car displays, and flash lights.

[0003] The reflective bracket in the LED component must have excellent whiteness and physical properties. Initially, the characteristics of ceramics are very suitable for this application, but the ceramic reflective bracket is extremely expensive and has extremely high post-processing requirements. Thermoplastic materials can make its structural design more flexible, and through multi-cavity mold injection molding, it greatly improves production efficiency. Subsequently, most ceramics were replaced by high-whiteness thermoplastic materials. Among thermoplastic materials, high-temperature resistant nylon is the most used. For example, the patent with publication number CN103890040A provides a high-whiteness polyamide composition. However, the LED reflective bracket will be exposed to high temperature during the manufacturing process or use. For example, during the manufacturing process, the LED emission bracket needs to be heated to about 180°C to cure the epoxy resin or silicon encapsulant; during SMT (surface mounting), the LED component will be exposed to a temperature higher than 260°C. High-temperature resistant nylon materials have obvious aging and yellowing problems due to their amide groups that easily react in a high-temperature oxygen atmosphere, thereby affecting their reflection effect on light.

[0004] Thermotropic liquid crystal polymers (TLCPs) are generally aromatic or semi-aromatic polyesters. The chemical bonds in their molecular structure are stable ester bonds, which form a conjugated effect with the benzene ring, making them have very excellent resistance to heat and oxygen aging, and show characteristics such as small color change after high-temperature aging. If thermotropic liquid crystal polymers can be used in LED components, the problem that LED components made of high-temperature resistant nylon materials are prone to yellowing due to high temperatures can be solved. However, the base color of the thermotropic liquid crystal polymer substrate is dark (beige), resulting in low whiteness, making it difficult to use as an LED component.

[0005] Therefore, the development of a TLCP material with high whiteness and resistance to high temperature yellowing will surely make it widely used in LED components. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problem that the current thermotropic liquid crystal polymer substrate has a dark base color and is difficult to be used as a material for LED components with high whiteness requirements, and to provide a liquid crystal polymer material. The liquid crystal polymer material uses a liquid crystal polymer resin as a base resin, adds a certain amount of titanium dioxide, and then adds a certain amount of PCT resin, and adjusts the mass ratio of titanium dioxide to PCT resin within a specific range, so as to obtain a liquid crystal polymer material with high whiteness, and the liquid crystal polymer material has excellent high temperature yellowing resistance.

[0007] A further object of the present invention is to provide a method for preparing the above liquid crystal polymer material.

[0008] A further object of the present invention is to provide the use of the above-mentioned liquid crystal polymer material in the preparation of LED reflective brackets, white connectors or appearance parts.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] A liquid crystal polymer material, comprising the following components in parts by weight:

[0011] Liquid crystal polymer resin 100 parts,

[0012] 40-125 parts of titanium dioxide,

[0013] 6 to 18.8 parts of PCT resin;

[0014] The mass ratio of the titanium dioxide to the PCT resin is 1:(0.1-0.2).

[0015] In the present invention, the liquid crystal polymer resin is a thermotropic liquid crystal polymer resin.

[0016] In the present invention, the mass ratio of the titanium dioxide to the PCT resin can be 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19 or 1:0.20, etc.

[0017] Titanium dioxide is a commonly used whitening colorant. In order to improve the whiteness of liquid crystal polymer materials, the inventors of the present invention tried to add titanium dioxide to liquid crystal polymer resins. However, when titanium dioxide is added to a certain proportion, the initial whiteness of the liquid crystal polymer material will not be further improved by adding more titanium dioxide. This is because the rigid molecular chain structure in the liquid crystal polymer resin and the ester group and the benzene ring form a conjugated effect, which makes the liquid crystal polymer molecular chain have a small polarity and poor wettability with titanium dioxide, making it difficult to achieve good coloring.

[0018] The inventor of the present invention has found through further research that, by adding a certain amount of titanium dioxide and then adding a certain amount of PCT resin (poly(1,4-cyclohexane terephthalate)), and adjusting the mass ratio of titanium dioxide to PCT resin within a specific range, a liquid crystal polymer material with high whiteness (initial whiteness higher than 90) can be obtained, and the liquid crystal polymer material has excellent high temperature yellowing resistance (whiteness retention rate after high temperature treatment higher than 90%), and is suitable for making LED components. The reason may be that PCT resin belongs to polyester, which has good compatibility with liquid crystal polymer resin, and a certain degree of ester exchange reaction will occur during the melt extrusion process, thereby introducing PCT molecular chains into the liquid crystal polymer resin molecular chains, changing the polarity of the liquid crystal polymer resin molecular chains, improving the wettability of the liquid crystal polymer resin with titanium dioxide, and thus achieving good coloring.

[0019] The amount of PCT resin added and the control of its mass ratio to titanium dioxide are particularly important. If the amount of PCT resin added is too little, resulting in a mass ratio of PCT resin to titanium dioxide of less than 0.1, it is difficult to effectively improve the initial whiteness of the liquid crystal polymer material; if the amount of PCT resin added is too much, resulting in a mass ratio of PCT resin to titanium dioxide greater than 0.2, the high temperature yellowing resistance of the liquid crystal polymer material will deteriorate. This is because: although PCT resin also has a certain yellowing resistance, it is still not comparable to liquid crystal polymer resin. If the amount of PCT resin is too much, the high temperature yellowing resistance of the obtained liquid crystal polymer material will deteriorate. The high temperature yellowing resistance of the liquid crystal polymer material will be poor, and it is also not suitable for making LED components and other parts.

[0020] Preferably, the liquid crystal polymer material comprises the following components in parts by weight:

[0021] Liquid crystal polymer resin 100 parts,

[0022] 60-100 parts of titanium dioxide,

[0023] 9 to 15 parts of PCT resin.

[0024] By optimizing the amount of each component, the initial whiteness and high temperature yellowing resistance of the liquid crystal polymer material can be better balanced, so that both are maintained at a high level.

[0025] Typically, the melt viscosity of the liquid crystal polymer resin is 15 to 25 Pa.s.

[0026] The melt viscosity of the liquid crystal polymer resin of the present invention can be measured according to ISO 11443-2014 standard using a capillary rheometer at T m +15℃、1000s -1 Measured under the conditions. m The melting point of .

[0027] Generally, the melting point of the liquid crystal polymer resin is 280-355°C.

[0028] The melting point of the liquid crystal polymer resin of the present invention can be measured according to ISO 11357-1-2016.

[0029] Typically, the volume average particle size of the titanium dioxide is 0.1 to 0.5 μm.

[0030] The volume average particle size of the titanium dioxide of the present invention can be measured according to ISO 8130-2019.

[0031] Preferably, the volume average particle size of the titanium dioxide is 0.2-0.4 μm. Within this range, the obtained liquid crystal polymer material has better initial whiteness and high temperature yellowing resistance.

[0032] Typically, the intrinsic viscosity of the PCT resin is 0.6 to 0.8 dL / g.

[0033] The intrinsic viscosity of the PCT resin of the present invention can be measured according to ISO 1268-5-2010.

[0034] Preferably, the intrinsic viscosity of the PCT resin is 0.65-0.75 dL / g. Within this range, the initial whiteness and high temperature yellowing resistance of the obtained liquid crystal polymer material are better.

[0035] Preferably, the liquid crystal polymer material further comprises 0.1 to 3 parts of other additives.

[0036] Optionally, the other auxiliary agent is at least one of an antioxidant or a lubricant.

[0037] Optionally, the antioxidant is selected from one or more of phenolic antioxidants, amine antioxidants, and sulfur antioxidants.

[0038] Optionally, the lubricant is selected from one or more of fluorine-containing polymers, linear low-density polyethylene (LLDPE), silicone oil, stearic acid metal salts, stearic acid alkyl esters, montanic acid metal salts, montanic acid ester wax or polyethylene wax.

[0039] The method for preparing the above-mentioned liquid crystal polymer material comprises the following steps:

[0040] The components are mixed uniformly, melted, extruded and granulated to obtain the liquid crystal polymer material.

[0041] The application of the above liquid crystal polymer material in the preparation of LED reflective brackets, white connectors or white appearance parts also falls within the protection scope of the present invention.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The present invention uses liquid crystal polymer resin as a base resin, adds a certain amount of PCT resin on the basis of adding a certain amount of titanium dioxide, and adjusts the mass ratio of titanium dioxide to PCT resin within a specific range, so as to obtain a liquid crystal polymer material with high whiteness, and the liquid crystal polymer material has excellent high temperature yellowing resistance. DETAILED DESCRIPTION

[0044] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0045] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0046] Liquid crystal polymer resin 1#: Zhuhai Wantong Special Engineering Plastics, Vicryst R8000 NC001, melting point T m The temperature is 280°C and the melt viscosity is 25 Pa.s;

[0047] Liquid crystal polymer resin 2#: Zhuhai Wantong Special Engineering Plastics, Vicryst R8500 NC001, melting point T m The temperature is 338°C and the melt viscosity is 25 Pa.s;

[0048] Liquid crystal polymer resin 3#: Zhuhai Wantong Special Engineering Plastics, Vicryst R800 NC001, melting point T m The temperature is 355°C and the melt viscosity is 25 Pa.s;

[0049] Liquid crystal polymer resin 4#: Zhuhai Wantong Special Engineering Plastics, Vicryst R800 NC002, melting point T m The temperature is 355°C and the melt viscosity is 15 Pa.s;

[0050] The melt viscosity of the liquid crystal polymer resin of the present invention can be measured by a capillary rheometer according to ISO 11443-2014 standard at T m1 +15℃、1000s -1 Measured under conditions.

[0051] Titanium dioxide 1#: volume average particle size 0.4 μm, brand R-900, purchased from DuPont;

[0052] Titanium dioxide 2#: volume average particle size 0.2 μm, brand R-104, purchased from DuPont;

[0053] Titanium dioxide 3#: volume average particle size 0.5 μm, brand BLR-886, purchased from Longbai Group;

[0054] PCT resin 1#: from SK Chemicals, 0302, intrinsic viscosity: 0.65 dL / g.

[0055] PCT resin 2#: from SK Chemicals, 0502, intrinsic viscosity: 0.75 dL / g.

[0056] PCT resin 3#: from Eastman Chemical Products Company, PCT36294, intrinsic viscosity: 0.625 dL / g.

[0057] Other additives: lubricant, linear low-density polyethylene, commercially available;

[0058] Unless otherwise specified, the components (such as other auxiliary agents) selected in the parallel examples and comparative examples are all the same commercially available products.

[0059] The performance of the liquid crystal polymer materials provided in the embodiments and comparative examples of the present invention was measured according to the following test methods:

[0060] Initial whiteness (W0) test: The sample was injection molded into a specimen with a size of 60×60×0.8 mm. The L, a, and b values ​​of the sample were measured using a ColorEye 7000A colorimeter, and the Hunter whiteness value was calculated using formula (1).

[0061] W=100-[(100-L) 2 +a 2 +b 2 ] 0.5 Formula (1)

[0062] High temperature yellowing test: The sample that has completed the initial whiteness (W0) test is placed at 200℃ for 6 hours, and its L, a, and b values ​​are measured again. The whiteness value after aging (W0) is calculated using formula (1). t ), whiteness retention rate W r =W t / W0×100%,W r The larger the value, the better the material's resistance to high temperature yellowing.

[0063] The preparation process of the liquid crystal polymer material of each embodiment and each comparative example of the present invention is as follows: the components are mixed uniformly, m The liquid crystal polymer material is melted, extruded and granulated at +10°C.

[0064] Examples 1 to 17

[0065] Examples 1 to 17 provide a series of liquid crystal polymer materials, whose formulas are shown in Table 1 and Table 2.

[0066] Table 1 Formulas of Examples 1 to 10 (parts by weight)

[0067]

[0068]

[0069] Table 2 Formulations of Examples 11 to 17 (parts by weight)

[0070]

[0071] Comparative Examples 1 to 5

[0072] Comparative Examples 1 to 5 provide a series of liquid crystal polymer materials, the preparation methods of which are the same as those of Example 1, and the formulations thereof are shown in Table 3.

[0073] Table 3 Formulas of Comparative Examples 1 to 5 (parts by weight)

[0074]

[0075]

[0076] The properties of the liquid crystal polymer materials of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 4.

[0077] Table 4 Performance test results of liquid crystal polymer materials of various embodiments and comparative examples

[0078]

[0079]

[0080] From Table 4, we can see that:

[0081] The initial whiteness of the liquid crystal polymer materials of Examples 1 to 17 can reach above 90, and the whiteness retention rate after high temperature treatment is above 90%, indicating that the liquid crystal polymer materials of the present invention have high whiteness and excellent high temperature yellowing resistance.

[0082] In Comparative Example 1, no PCT resin was added, and the initial whiteness of the obtained liquid crystal polymer material was 84.8, which was significantly lower. In Comparative Example 2, too little titanium dioxide was added, and the initial whiteness of the obtained liquid crystal polymer material was lower (87.9). In Comparative Example 3, too much titanium dioxide was added, and the corresponding amount of PCT resin added was also more, and the yellowing resistance of the obtained liquid crystal polymer material was poor. In Comparative Example 4, too little PCT resin was added, and the initial whiteness of the obtained liquid crystal polymer material was lower (88.7). In Comparative Example 5, too much PCT resin was added, and the yellowing resistance of the obtained liquid crystal polymer material was poor.

[0083] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A liquid crystal polymer material, characterized in that: The composition comprises the following components in parts by weight: Liquid crystal polymer resin 100 parts, 40-125 parts of titanium dioxide, 6 to 18.8 parts of PCT resin; The mass ratio of the titanium dioxide to the PCT resin is 1:(0.1-0.2).

2. The liquid crystal polymer material according to claim 1, characterized in that: The liquid crystal polymer material comprises the following components in parts by weight: Liquid crystal polymer resin 100 parts, 60-100 parts of titanium dioxide, 9 to 15 parts of PCT resin.

3. The liquid crystal polymer material according to claim 1, characterized in that: The melt viscosity of the liquid crystal polymer resin is 15 to 25 Pa.s.

4. The liquid crystal polymer material according to claim 1, characterized in that: The melting point of the liquid crystal polymer resin is 280-355°C.

5. The liquid crystal polymer material according to claim 1, characterized in that: The volume average particle size of the titanium dioxide is 0.1 to 0.5 μm.

6. The liquid crystal polymer material according to claim 1, characterized in that: The intrinsic viscosity of the PCT resin is 0.6-0.8 dL / g.

7. The liquid crystal polymer material according to claim 1, characterized in that: The liquid crystal polymer material also includes 0.1 to 3 parts of other auxiliary agents.

8. The liquid crystal polymer material according to claim 7, characterized in that: The other auxiliary agent is at least one of an antioxidant and a lubricant.

9. The method for preparing the liquid crystal polymer material according to any one of claims 1 to 8, characterized in that: The steps include: The components are mixed uniformly, melted, extruded and granulated to obtain the liquid crystal polymer material.

10. Use of the liquid crystal polymer material according to any one of claims 1 to 8 in the preparation of LED reflective brackets, white connectors or white appearance parts.

Citation Information

Patent Citations

  • Improved polyamide compositions for LED applications

    CN103890040A